A review of current practice for testing by analysis of cold-formed steel structures. (March 2022) - Koh, Hyeyoung; Blum, Hannah B.
Graphical abstract: Highlights: Review of current practice for numerical test-based design of cold-formed steel and other industries. Recommendations for the use of testing by analysis in cold-formed steel design. Example of using testing by analysis for cold-formed steel design in recent research. Abstract: New product development is crucial to advance innovation in the cold-formed steel structural industry. Design of cold-formed steel structures usually requires physical testing, but it may be challenging to control the complexity and uncertainty inherent in physical experiments. The physical testing of new components and assemblies is often a cost barrier that prevents implementation and delays new product development. Testing by analysis has recently been recognized as a desirable area to pursue by the cold-formed steel structural industry due to the benefit of providing an efficient test environment. Not only does testing by analysis limit the high expense of physical experiments needed to quantify the behavior and safety of new members, connections, and structures, but it also reduces the time from product inception to development. Two considerations are necessary to ensure accurate results from testing by analysis. First, it requires a rational engineering analysis to calculate the capacities and deformations of the member or system, and the requirements to produce accurate analyses must be explicitly stated. Second, it is necessary to understand if the software used is capable of correctly modeling the behavior of thin-walled and nonsymmetric structural members and systems. Although the computational capability for structural design has been developed in recent years, there lacks a standardized approach to testing by analysis, especially for cold-formed steel design. This review aims to evaluate existing design standards that include the numerical test-based design for both cold-formed steel and other structural engineering industries. Recommendations for the use of testing by analysis based on the design standards and recent research related to numerical modeling are presented. The results of this study will assist with accurate and efficient design using testing by analysis.